Meiosis-specific localization of the exocytic Rab Ypt2 in fission yeast - Imada, Kazuki (Small GTPases, 2017)
Fission yeast Ypt2, an orthologue of the mammalian small GTPase Rab8, is responsible for post-Golgi membrane trafficking. During meiosis, Ypt2 localizes at the spindle pole body (SPB), where it regulates de novo biogenesis of the spore plasma membrane. Recruitment of Ypt2 to the SPB is dependent on its meiosis-specific GDP/GTP exchange factor (GEF), the SPB-resident protein Spo13. Here we have examined the SPB recruitment of Ypt2 by Spo13. The GEF activity of Spo13 was required, but not essential for recruitment. Furthermore, Ypt2 recruitment was regulated in a meiosis-specific manner and partially regulated by the nuclear Dbf2-related (NDR) kinase Sid2, indicating the existence of a novel regulatory mechanism for localization of Rab GTPases during meiosis.